2020
DOI: 10.1038/s43246-020-0029-y
|View full text |Cite
|
Sign up to set email alerts
|

Rapid three-dimensional structuring of transparent SiO2 glass using interparticle photo-cross-linkable suspensions

Abstract: Photo-curable suspensions are important materials for shaping complex-structured ceramic and glass components. However, most systems undergo slow debinding and sintering so to avoid structural collapse by rapid gas generation from polymers. Here, we propose a new strategy to fabricate interparticle photo-cross-linkable suspensions for rapid threedimensional structuring with short debinding and sintering times. SiO 2 particles modified with polyethyleneimine complexed with oleic acid (PEI-OA) are dispersed into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 50 publications
1
25
0
Order By: Relevance
“…First, we confirmed that it was possible to obtain a uniform material without using a sensitizer. We previously developed several types of stereolithography systems, for example, a bottom-up system based on single-photon polymerization using a blue laser, direct writing system using a blue laser and/or a femtosecond laser. , In this study, we used a 375 nm laser instead of a blue laser in a bottom-up stereolithography system (Figure ). In most of their reports on RAFT-based optical fabrication methods, Bagheri et al and Boyer et al used commercially available digital light processing (DLP)-type optical fabrication systems. , In contrast, we used a laboratory-constructed laser-scanning stereolithography (SLA) system.…”
Section: Resultsmentioning
confidence: 99%
“…First, we confirmed that it was possible to obtain a uniform material without using a sensitizer. We previously developed several types of stereolithography systems, for example, a bottom-up system based on single-photon polymerization using a blue laser, direct writing system using a blue laser and/or a femtosecond laser. , In this study, we used a 375 nm laser instead of a blue laser in a bottom-up stereolithography system (Figure ). In most of their reports on RAFT-based optical fabrication methods, Bagheri et al and Boyer et al used commercially available digital light processing (DLP)-type optical fabrication systems. , In contrast, we used a laboratory-constructed laser-scanning stereolithography (SLA) system.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the photo-responsive suspensions were obtained by degassing the suspension via centrifugation (2200 rpm, 3 min) after removing the balls. Some SiO 2 suspensions were doped with metal ions (0.15 mol % Eu 2+ and Tb 3+ , based on the number of PEI monomer units, respectively) through their complex formation with the amino groups of PEI-OA, similarly to our previous report …”
Section: Methodsmentioning
confidence: 94%
“…First, the PEI-OA complex (15 mol % OA in PEI monomer units, calculated assuming all amines to be secondary amines) was prepared in a manner similar to that in our previous reports. Briefly, 0.500 g of PEI and 0.493 g of OA corresponding to 15 mol % OA were mixed with α-terpineol to prepare a 10.0 g solution. The obtained solution was treated in an ultrasonic bath for 5 min and magnetically stirred for 24 h. The PEI-OA was then dissolved in a mixed solution of α-terpineol and THF (45 vol %), and the refractive index was tuned to match with SiO 2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Binder jet additive manufacturing (BJAM) is well suited for manufacturing these tools and dies due to its high production rates, low operator burden, high resolution, and ability to process low-cost feedstocks, such as sand 6 . BJAM is an AM process that uses a layer-by-layer polymer binding process to rapidly manufacture complex three-dimensional tools and dies at significantly higher throughput when compared with directed-energy binding AM methods 6 , 7 . Selective inkjetting is used to deliver the binding polymer into the layers of powder to bind the powdered materials together (Fig.…”
Section: Introductionmentioning
confidence: 99%